The effects of whirlpool bath and neuromuscular electrical stimulation on complex regional pain syndrome - Devrimsel, Gul; Turkyilmaz, Aysegul Kucukali; Beyazal, Munevver Serdaroglu; Yildirim, Murat (Journal of Physical Therapy Science, 2015)
[Purpose] The aim of the present study was to investigate and compare the effects of whirlpool bath and neuromuscular electrical stimulation on complex regional pain syndrome. [Subjects and Methods] Sixty outpatients (30 per group) with complex regional pain syndrome participated. They received 15 treatment 5 days per week for 3 weeks. The outcome measures were the visual analogue scale for pain, edema, range of motion of the wrist (flexion and extension), fingertip-to-distal palmar crease distance, hand grip strength, and pinch strength. All parameters were measured at baseline (week 0) and at the trial end (week 3). [Results] There were significant improvements in all parameters after therapy in both groups. The whirlpool bath group showed significantly better improvements in the visual analogue score, hand edema, hand grip strength, wrist range of motion (both flexion and extension), fingertip-to-distal palmar crease distance, and the three-point and fingertip pinch strengths than the neuromuscular electrical stimulation group; however, the lateral pinch strengths were similar. [Conclusion] Both whirlpool bath and neuromuscular electrical stimulation are effective in the treatment of complex regional pain syndrome, but the efficacy of the whirlpool bath treatment was better.